The DELLA Proteins Influence the Expression of Cytokinin Biosynthesis and Response Genes During Nodulation - Dolgikh, Alexandra V.; Kirienko, Anna N.; Tikhonovich, Igor A.; Foo, Eloise; Dolgikh, Elena A. (Frontiers in Plant Science, 2019)
The key event that initiates nodule organogenesis is the perception of bacterial signal molecules, the Nod factors, triggering a complex of responses in epidermal and cortical cells of the root. The Nod factor signaling pathway interacts with plant hormones, including cytokinins and gibberellins. Activation of cytokinin signaling through the homeodomain-containing transcription factors KNOX is essential for nodule formation. The main regulators of gibberellin signaling, the DELLA proteins are also involved in regulation of nodule formation. However, the interaction between the cytokinin and gibberellin signaling pathways is not fully understood. Here, we show in Pisum sativum L. that the DELLA proteins can activate the expression of KNOX and BELL transcription factors involved in regulation of cytokinin metabolic and response genes. Consistently, pea la cry-s (della1 della2) mutant showed reduced ability to upregulate expression of some cytokinin metabolic genes during nodulation. Our results suggest that DELLA proteins may regulate cytokinin metabolism upon nodulation.